THE URGENCY OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) IN ISLAMIC LEARNING IN FACE-TO-FACE LEARNING MANAGEMENT IN PRESCHOOL / KINDERGARTEN - Siti Bulkis; Adiyono Adiyono (International Journal of Teaching and Learning, 2024)
The world of education must always adapt technological developments to efforts to improve the quality of education, especially adjusting the use of information and communication technology for the world of education, especially in the learning process. The world is in a phase of rapid technological development. The utilization/use of ICT-based learning media which is rich and varied in various types and characteristics, not only increases interest and motivation in learning, but learning can increase children's interest in learning and be meaningful/inspirational. In this research, the author used qualitative research as a literature study. The research stages were carried out by collecting library sources, both primary and secondary. Learning media created based on augmented reality is suitable for use in early childhood and is a solution in implementing the learning process. This learning media can help cognitive development in children aged 4-5 years. In the learning process, teachers or educational teams should be more sensitive to technological developments, especially now that teachers are dealing with students in the alpha generation. Teachers can use various types of applications that support the learning process in the Early Childhood education unit in the learning process. So this will make it easier for teachers and children to understand the purpose of this learning.